The Fear of God and the Classification of Science: Abraham bar Ḥiyya (d. ca. 1140) and the Andalusi Reception of Al-Fārābī’s Enumeration of the Sciences (Iḥṣāʾ al-ʿulūm) - González Diéguez, Guadalupe (Théologiques, 2021)
This article traces the association between wisdom and the fear of God in two encyclopedias of science that circulated in medieval Iberia: Enumeration of the Sciences by al-Fārābī and The Foundations of Intelligence and the Tower of Faith by Bar Ḥiyya. It offers insight into the polemical reception of al-Fārābī's work in the Iberian Peninsula; an analysis of Bar Ḥiyya's introduction to his encyclopedia, in which the fear of God occupies a central place; and an analysis of the epilogue of the only Andalusian manuscript that preserves al-Fārābī’s Enumeration, which also emphasizes the fear of God. The article argues that al-Fārābī's rather scandalous reputation in al-Andalus could explain the framing of his classification of the sciences, and those inspired by it, with pious considerations on the fear of God as a necessary condition to the study of science.